1998
DOI: 10.1539/joh.40.193
|View full text |Cite
|
Sign up to set email alerts
|

Liver Damage among Environmental Disinfestation Workers

Abstract: Abstract:Liver Damage among Environmental Disinfestation Workers: Francesco TOME1, et al. OccupationalMedicine Dept., "La Sapienza" University, Rome-It has been reported that exposure to high doses of insecticides can damage the liver. It is now becoming apparent that even exposure to low doses may affect the liver and blood. Studies on the effects on the health of disinfestation workers are scant. This study investigated 37 males doing environmental disinfestation work. They all employed the same types and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…A similar increase in the AST and ALT levels was reported in agricultural workers in India (Patil et al, 2003) and selected farm workers in Gadap Karachi, Pakistan (Azmi et al, 2006). Tomei et al (1998) also reported considerable liver damage with significant increase in AST, ALP and total bilirubin among environmental disinfectant workers in Italy. High degree of abnormal liver function in workers may indicate toxic effects of pesticides and the presence of pesticide residues in blood (Amr, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…A similar increase in the AST and ALT levels was reported in agricultural workers in India (Patil et al, 2003) and selected farm workers in Gadap Karachi, Pakistan (Azmi et al, 2006). Tomei et al (1998) also reported considerable liver damage with significant increase in AST, ALP and total bilirubin among environmental disinfectant workers in Italy. High degree of abnormal liver function in workers may indicate toxic effects of pesticides and the presence of pesticide residues in blood (Amr, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…Similar observations have been made by Al-Sarar et al (2009). Nevertheless, significant increase in the levels of these enzymes was seen in occupationally exposed workers (Tomei et al 1998;Khan et al 2008Khan et al , 2009Khan et al , 2010; and in sprayers of grape gardens in India (Patil et al 2003). Plasma AChE activity has been used for several years as indicator to estimate the risks associated with pesticides induced toxicity in occupationally exposed workers (Dasgupta et al 2007;Khan et al 2008; Shalaby&Abd El-Mageed 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, all poisoning is dose dependent and toxic response depends on the size of the dose in relation to the size of the victim and extent of exposure. It has been reported that exposure to high doses of insecticides can damage the liver (Tomei et al, 1998).…”
Section: Introductionmentioning
confidence: 99%